An improved decentralized control strategy for a PV hybrid energy storage system in an LVDC microgrid - Li, Jianbiao; Chen, Yong; Wu, Yue; Cheng, Xu; Yang, Ruixiong (Frontiers in Energy Research, 2024)
This paper introduces an improved decentralized control strategy for a photovoltaic (PV) hybrid energy storage (HES) system (HESS) in a DC microgrid. The power sharing method of the HES system is discussed in depth. The basic principle of virtual resistance and capacitance droop (VRCD) control, which consists of virtual resistance droop (VRD) and virtual capacitance droop (VCD) control, is analyzed in detail to achieve the decoupling of the HES system for high- and low-frequency load power distribution. For the virtual capacitance control loop, the voltage compensator is added to achieve terminal voltage restoration of the supercapacitor (SC). For the virtual resistance control loop, in order to solve the problems of the unbalanced state of charge (SOC) of battery storage, a virtual resistance droop control based on a novel adaptive function is introduced. Finally, a model of the HESS in a DC microgrid is built in a real-time emulator to verify the effectiveness of the proposed control strategy.